Oiling the gate: a mobile application to improve the admissions process from the emergency department to an academic community hospital inpatient medicine service. Issue 1 (2nd January 2018) - Fung, Russell; Hyde, Jensen Hart; Davis, Mike
ABSTRACT: The process of admitting patients from the emergency department (ED) to an academic internal medicine (AIM) service in a community teaching hospital is one fraught with variability and disorder. This results in an inconsistent volume of patients admitted to academic versus private hospitalist services and results in frustration of both ED and AIM clinicians. We postulated that implementation of a mobile application (app) would improve provider satisfaction and increase admissions to the academic service. The app was designed and implemented to be easily accessible to ED physicians, regularly updated by academic residents on call, and a real-time source of the number of open AIM admission spots. We found a significant improvement in ED and AIM provider satisfaction with the admission process. There was also a significant increase in admissions to the AIM service after implementation of the app. We submit that the implementation of a mobile app is a viable, cost-efficient, and effective method to streamline the admission process from the ED to AIM services at community-based hospitals.